Note: European Consumers' Perceptions of Time–Temperature Indicators in Food Packaging. Issue 12 (December 2016) - Pennanen, Kyösti; Focas, Caralampo; Kumpusalo‐Sanna, Vilja; Keskitalo‐Vuokko, Kaisu; Matullat, Imke; Ellouze, Mariem; Pentikäinen, Saara; Smolander, Maria; Korhonen, Virpi; Ollila, Margareetta
Abstract : The article from this special issue was previously published in Packaging Technology in Science, Volume 28, Issue 4, 2015. For completeness we are including the title page of the article below. The full text of the article can be read in Issue 28:4 on Wiley Online Library:http://onlinelibrary.wiley.com/doi/10.1002/pts.2105/abstract